Couette flow problem for an unsteady MD third-grade fluid with hall currents - Azram, Mohammad; Zaman, Haider (IIUM Press, 2014)
In this work, we analyze Coutte flow problem for an unsteady mangnetohydrodynamic (MHD) third-grade fluid in the presence of a pressure gradient and Hall currnts. Existing literature on the topic shows that the effecs of Hall current on Coutte flow of an unsteady MHD third-grade fluid with a prssure gradient has not yet beeninvestigated. The arising non-linear problem is solved by the homotopy analysis method (HAM) and the convergence of the obtained complex series solution is carefully analyzed. The effects of pressure number, Hartmann number and Hall parameter on unsteady velocity are discussed via analysis of plots. ABSTRAK: Kajian dijalan untuk menganalisa masalah aliran Coutte bagi bendalir MHD gred ketiga dan arus Hall. Bagi topik ini kesan arus Hall terhadap aliran Couette dalam bendalir MHD gred ketiga tak mantap dengan kecerunan tekanan, belum pernah dikaji selidik. Masalah tak linear berbangkit diselesaikan dengan kaedah analisis homotopi (HAM) dan ketumpuan solusi rangkaian kompleks dianalisa dengan teliti. Kesan nilai tekanan, nombor Hartmann dan parameter Hall terhadap halaju tak mantap diperbincangkan melalui plot yang dianalisis.